Planet Earth : bite-size facts to make learning fun and fast - "Richards, Jon" (London; Mortimer Children's Books, 2021)
This book is full of essential info about the planet we live on, broken down into fun bite-size facts. Learn everything about Planet Earth in 60 seconds! Key earth sciences like geography, geology, ecology and natural history are clearly explained using colourful graphics and easy-to-follow text. Scattered throughout the book are 'Now Try This!' panels where readers can take their understanding even further by carrying out simple activities and projects. There's even a pullout wallchart to record their progress in each subject. Readers will learn everything there is to know about their planet in record time!
Donated from "Book Planet", Dated 18-4-2025.
Keywords: Earth sciences